Shopping tourism: comparative analysis of the cities of Oporto and Lisbon as shopping destinations - Liberato, Dália (2020)
Shopping tourism is becoming more and more important in the tourism value chain. Shopping is already a determining factor in the decision to travel and the choice of destination. Due to social, cultural and economic changes around the world, there are new patterns of consumption and purchasing behaviours. The general objective of this study is to compare data between the two largest and important Portuguese tourist cities, Lisbon and Oporto, in the context of shopping tourism. The specific objectives are to interpret the factors that influence the intention of spending in the destination and to investigate the role of the attributes of purchases in the behavioural intention in the context of the destination. To answer the objectives of this research, a questionnaire was created and applied to 1097 tourists/visitors, in the cities of Lisbon and Oporto. Of the 1097 respondents, 606 answered the questionnaire regarding Lisbon and 491 answered the questionnaire applied in Oporto. In both samples, total expenditures and purchases increase for those who perform more purchases due to the Tax-free system. Total spending and purchases increase for those who agree more with the fact that the Tax-Free system allows to spend less money on purchases, what happens in both samples, and that Lisbon is a competitive shopping destination due to the Tax-Free system, which evidently happens only in the Lisbon sample. In the two samples, the “service side” positively influences the “reliability of the products” and “credibility”.